Analisis Komparasi Expected Return dan Risiko antara Saham IDX30 Dengan Saham Non IDX30 serta Pembentukan Portofolio Optimal - Ahita, Siti Ayomi (Jurnal Ilmiah Mahasiswa FEB, 2017)
The purpose of this study is to determine the differences of expected return, and risk on IDX30 stock and Non IDX30 stock in Indoneseia Stock Exchange from May 2012 till July 2016, and to investigate the correlation between return and risk. Then,construct the optimal portfolio by using the best stock group. Â This study using quantitative approach with independent sample t test, pearson correlation., and using single index model to construct the optimal portfolio. Determination of sample using non probability sampling. Data that being used was secondary data. The result of this study showed that there was significant differences of expected return, and risk on IDX30 stock and Non IDX30 stock. Non IDX30 stock has bigger average number of expected return and risk compared to IDX30 stock. And in this study, showed that there was a correlation betweed expected return and risk. The optimal portfolio consist of five stocks, the optimal portfolio comprises 57% for ABDA, 20% for SMMA, 14% for PANR, 6% for LPGI, and 3% for MTDL.Keywords : Single index model, IDX30, independent sample t test, expected return, risk, deviation standard, optimal portfolio, correlation.